วิเคราะห์ต้นทุนและผลประโยชน์ทางเศรษฐศาสตร์ของการปลูกข้าวพันธุ์ญี่ปุ่นแบบเกษตรพันธะสัญญาของบริษัทแห่งหนึ่ง ในจังหวัดเชียงราย - ภคพร บุญมหาธนากร (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The objective of this study is to analyze economic costs and benefits, also economic rate of return of a Japonica Rice Contract Farming in Chiang Rai Province. Economic cost include fixed cost, variable cost, environment and health costs from using chemical. Economic benefits involve direct revenue from sale, indirect benefits from reducing imports of Japanese rice, increasing income to the community, and reducing subsidies in rice mortgage scheme. Regarding to the analysis of 8 years project in base case, the results of financial internal rate of return (FIRR) and economic internal rate of return (EIRR) are found to be 24% and 140.3%, respectively which higher than discount rate of 7%. In addition, the financial net present value (FNPV) and economic net present value (ENPV) are discovered to be 26,105,308 and 153,147,796 Baht, respectively. Thus, those imply that the project is worthy for investment. Moreover, the results of sensitive analysis for financial and economic reveal that the increase in costs and a decrease in benefits in all cases are worth for investment and could withstand risks. In the case of financial analysis, the variable costs could increase up to 29.9% and the benefits could decrease up to 20.8%. In case of economics, the variable costs could increase up to 175.2% and the benefits could decrease up to 60%. Therefore, the policy makers of public sector should work in partnerships with private sector to launch the measures to strongly and continuously support this project.